2019
DOI: 10.35808/ijeba/227
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Organizational Commitment on Job Performance

Abstract: Purpose: This research discusses the direct effect of multicultural competencies, organizational fairness and organizational commitment on job performance. The primary data was collected using explanatory survey. Design/Methodology/Approach: The sample consists of 350 respondents who are civil servants in Central Lampung Regency, Metro municipality and East Lampung Regency. The requirement analysis test used normality Lilliefors, homogeneity, linearity and significance regression. The data analysis technique i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 21 publications
(49 reference statements)
7
74
1
11
Order By: Relevance
“…This study also found that effective commitment plays a vital role as mediators in GCG and KM effect on professional performance. This evidence in line with studies concluded that GCG influences affective commitment [56] [57], KM influences affective commitment [58]- [61], and affective commitment affects professional performance [47]- [55]. This finding reveals empirical facts that the existence of affective commitment is very important to be considered in the context of increasing professional performance through GCG and KM.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This study also found that effective commitment plays a vital role as mediators in GCG and KM effect on professional performance. This evidence in line with studies concluded that GCG influences affective commitment [56] [57], KM influences affective commitment [58]- [61], and affective commitment affects professional performance [47]- [55]. This finding reveals empirical facts that the existence of affective commitment is very important to be considered in the context of increasing professional performance through GCG and KM.…”
Section: Discussionsupporting
confidence: 88%
“…The studies conducted by scholars in various fields also indicated that KM affects affective commitment [58]- [61]. Meanwhile, the research in other contexts carries out by researchers show that affective commitment affects professional performance [47]- [55]. Based on argues and studies above, the seventh hypothesis in this study is: H 7 : KM had an indirect effect on professional performance mediating by affective commitment.…”
Section: Km and Professional Performance Mediating By Affective Commimentioning
confidence: 71%
See 3 more Smart Citations